2013
DOI: 10.1038/ncomms3655
|View full text |Cite
|
Sign up to set email alerts
|

Huge critical current density and tailored superconducting anisotropy in SmFeAsO0.8F0.15 by low-density columnar-defect incorporation

Abstract: Iron-based superconductors could be useful for electricity distribution and superconducting magnet applications because of their relatively high critical current densities and upper critical fields. SmFeAsO 0.8 F 0.15 is of particular interest as it has the highest transition temperature among these materials. Here we show that by introducing a low density of correlated nano-scale defects into this material by heavy-ion irradiation, we can increase its critical current density to up to 2 Â 10 7 A cm À 2 at 5 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 38 publications
7
57
0
Order By: Relevance
“…Here most of the experiments were carried out on single crystal samples, and Jc was determined by magnetic hysteresis loop (MHL) measurements. To summarize the results, (1) Jc of Fe-based superconductors is generally high: Jc ~ 2 MA/cm 2 at 5 K and 0 T for SmFeAsO1-xFx [11], ~ 2 MA/cm 2 for KBa122 [24], ~ 0.1 MA/cm 2 for LiFeAs [25], and ~ 0.2 MA/cm 2 for FeTe1-xSex [26], respectively. (2) The MHL measurements show a sharp peak at around zero field and a power-law decay of Jc at low-field region, which are attributed to the strong pinning [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here most of the experiments were carried out on single crystal samples, and Jc was determined by magnetic hysteresis loop (MHL) measurements. To summarize the results, (1) Jc of Fe-based superconductors is generally high: Jc ~ 2 MA/cm 2 at 5 K and 0 T for SmFeAsO1-xFx [11], ~ 2 MA/cm 2 for KBa122 [24], ~ 0.1 MA/cm 2 for LiFeAs [25], and ~ 0.2 MA/cm 2 for FeTe1-xSex [26], respectively. (2) The MHL measurements show a sharp peak at around zero field and a power-law decay of Jc at low-field region, which are attributed to the strong pinning [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the introduction of artificial pinning centers by irradiation with heavy-irons, neutrons, electrons, etc. largely enhances Jc [9][10][11][12]. At this moment, the improvement of inter-grain connectivity is one of the challenges for applications such as powder-in-tube wires and tapes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various iron based superconductors, 122-type (AE)Fe 2 As 2 (AE = Sr, Ba) is very attractive for high field applications due to its excellent properties such as very high upper critical field (H c2 ), relatively small anisotropy [10,11], and an advantageous grain-boundary nature [12]. In order to achieve high critical current density (J c ) various processing techniques have been used [13][14][15][16][17][18]. Among these proposed processes, the powder-in-tube (PIT) method seems the most promising technique for practical applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The stronger intra-grain pinning observed in the 1111 HTSC-Fe family compared to the 11-HTSC Fe and its technological control via correlated nanoscale defects [64] will have application relevance. However keep in mind that in the fabrication of the superconducting wires and tapes the limiting factor of the critical current are mainly the grain boundaries, then as a first step need solve this technologically relevant fact [65].…”
Section: Resultsmentioning
confidence: 99%